Prickly Pear Cactus Control in Pastures - Brent Sellers; Pratap Devkota; Jason Ferrell (EDIS)
Prickly pear cactus is not a problem in every pasture in Florida, but where it is found, it is often the biggest and most difficult issue to manage. Written by Brent Sellers, Pratap Devkota, and J. Ferrell, and published by the UF/IFAS Agronomy Department, revised July 2020.